Methanogenesis inhibition remodels microbial fermentation and stimulates acetogenesis in ruminants - Gaofeng Ni; Min Wang; Nicola Walker; Stefan Muetzel; Oliver Schmidt; Andre Fischer; René T. Stemmler; Pok Man Leung; Xiumin Zhang; Qiushuang Li; Surbhi Jain; Marion Jespersen; et al. (Proceedings of the National Academy of Sciences, 2025)
Rumen microbiota enable ruminants to grow on fibrous plant materials, but also produce methane, driving 5% of global greenhouse gas emissions and leading to a loss of gross energy content. Methanogenesis inhibitors such as 3-nitrooxypropanol (3-NOP) decrease methane emissions in ruminants when supplemented in feed. Yet we lack a system-wide, species-resolved understanding of how the rumen microbiota remodels following inhibition and how this influences animal production. Here, we conducted a large-scale trial with 51 dairy calves to analyze microbiota responses to 3-NOP, pairing host performance, emissions, and nutritional profiles with genome-resolved metagenomic and metatranscriptomic data. 3-NOP supplementation decreased methane emissions by 62%, modulated short-chain fatty acid and H 2 levels, and did not affect dietary intake or animal performance. We created a rumen microbial genome catalogue (27,884 genomes) that mapped to the meta-omic data at high rates. There was a strong reduction of methanogens and stimulation of reductive acetogens, primarily uncultivated lineages such as “ Candidatus Faecousia.” However, there was a shift in major fermentative communities away from acetate production in response to hydrogen gas accumulation. In vitro incubations recapitulated these results and showed an enrichment of acetate from reductive acetogenesis. Altogether, the divergent responses of the fermentative and hydrogenotrophic communities lead to net hydrogen build-up and limit potential productivity gains from methane reduction. By linking ruminant greenhouse gas emissions and productivity to specific microbial species, this study emphasizes the importance of microbiota-wide analysis for optimizing methane mitigation strategies and identifies promising strategies to simultaneously reduce emissions while increasing animal production.